2011
DOI: 10.1002/jor.21443
|View full text |Cite
|
Sign up to set email alerts
|

Are polymorphisms of molecules involved in bone healing correlated to aseptic femoral and tibial shaft non‐unions?

Abstract: Fracture healing is a well-organized process between several molecules and mediators. As known from other diseases, genetic polymorphisms may exhibit different expression patterns in these mediators. Concerning fracture healing, this may lead to an extended healing process or non-union. We investigated the incidence of polymorphisms in patients with aseptic non-unions after femoral and tibial shaft fractures as compared to patients with uneventful healing. Exclusion criteria were smoking, diabetes, bilateral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…In the present study, the presence of the G allele at SNP rs3819089 on the MMP13 gene was found to be protective from nonunion (OR = 0.26, p = 0.026). Zeckey et al found a similar result in their earlier study 43 .…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, the presence of the G allele at SNP rs3819089 on the MMP13 gene was found to be protective from nonunion (OR = 0.26, p = 0.026). Zeckey et al found a similar result in their earlier study 43 .…”
Section: Discussionsupporting
confidence: 73%
“…Earlier studies demonstrated a possible BMP-related genetic predisposition for impaired fracture healing (e.g. in the BMP inhibitor noggin) [11][12][13]. Consequently, low basal levels of BMPs should be determinable even years after the fracture has healed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the BMP4 expression increases significantly during fracture healing and in cases of fibrodysplasia ossificans progressiva in humans . Previous studies have shown that C > T polymorphism in BMP4 rs17563 is associated with ossification of the posterior longitudinal ligament, but show no association with fracture NU …”
mentioning
confidence: 99%